Positive design Delft students design for our well-being Volume 2 - Desmet, Pieter (2020)
In 2015, a new journal was launched: the Dutch Journal of Positive Psychology. The editor-in-chief invited me to contribute with a regular column that reflects on the question of how design can contribute to the field of positive psychology. I was immediately excited because I saw an opportunity to share some of our students' inspiring work with a wider audience. Hence, we agreed that the columns would serve to present examples of Positive Design - design cases that focus on human flourishing, by students and researchers of the TU Delft Faculty of Industrial Design Engineering. Over the years, I have witnessed how an increasing number of design students have become inspired by the concept of well-being. These are designers who aspire to consciously and deliberately use their design skills in contributing to the happiness of individuals and communities. Rather than being a fortuitous by-product of design, well-being has firmly anchored itself in the heart of these students' design intentions. I hope the columns convey some of their irrepressible enthusiasm. This is the second edition of the Positive Design booklet. It presents columns 11 to 19, written between 2018 and 2020. Some of the design cases focus on individuals, others on groups. Some help us to rediscover our talents, some support us in forming meaningful relationships, and others enable us to invest in our own happiness and that of those we care about.